Analysis of Implementation and Perception of Online Formative Assessment on Students’ Speaking Skill at Sukasada - Gautami, Gusti Ayu Agung Tania; Santosa, Made Hery (STKIP AGAMA HINDU SINGARAJA, 2021)
This study investigated the perspective and the implementation of formative assessments by the teacher to the students in the SMPN 1 Sukasada. There were 1 English teacher and 11 students investigated as the informants. The data gained through closed-ended questionnaires and the teacher was interviewed by using Whatsapp chat. The result of this study shows that the teacher cannot assess the students’ speaking skill during this pandemic. In the point of view of students, they thought that speaking is important but, they do not have any gadgets to support their improvement in speaking skill. Based on this result the teacher has important role in developing the students’ language skills in order to achieve the objectives of the learning. The students also should be able to manage themselves during online learning. It is very challenging for both of participants in achieving the successes of the learning objectives